Clinical and symptomatological characterization regarding Chagas disease caused by the Trypanosoma cruzi parasite (Research, Society and Development, 2021)
Neglected diseases are a group of communicable diseases that mainly affect tropical regions of developing countries. Among this group of diseases is Chagas disease, which has been classified among the six most important parasitic diseases in the world, and it is estimated that more than one billion people are at risk in endemic countries. The objective of this study is to review the literature on the symptomatological and clinical characterization of Chagas disease caused by Trypanosoma cruzi. This is an integrative literature review study. For this, we used the following descriptors in the search: Trypanosoma cruzi, epidemiological profile, Chagas disease and clinical aspects (together and separately). In the selection criteria we opted for full articles, in the period 2013 - 2021 (last 9 years), in Portuguese and English. The searches were conducted in the following databases: Scientific Electronic Library Online (Scielo), Pubmed, Latin American and Caribbean Literature on Health Sciences (Lilacs), Google Scholar. The articles were selected first by title, then by abstract, and finally by complete reading. The literature shows that Chagas disease is caused by the protozoan Trypanosoma cruzi, characterized by the presence of a flagellum and kinetoplast. Some of its clinical manifestations include: fever, asthenia, adynamia, myalgia, arthralgia, headache, myocarditis, and hepatosplenomegaly. Therefore, it is important to know all the characteristics of this disease, since it can be considered a public health problem. It is suggested that new studies be carried out with different approaches, in order to elucidate even more specifically the dynamics surrounding this disease.